2014
DOI: 10.1080/09168451.2014.891935
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression, purification, and characterization of Paenibacillus cell surface-expressed chitinase ChiW with two catalytic domains

Abstract: Paenibacillus sp. strain FPU-7 produces several different chitinases and effectively hydrolyzes robust chitin. Among the P. FPU-7 chitinases, ChiW, a novel monomeric chitinase with a molecular mass of 150 kDa, is expressed as a cell surface molecule. Here, we report that active ChiW lacking the anchoring domains in the N-terminus was successfully overproduced in Escherichia coli and purified to homogeneity. The two catalytic domains at the C-terminal region were classified as typical glycoside hydrolase family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…FPU-7 (Fig 1) were overexpressed in Escherichia coli ( E . coli ) and purified as described previously [12]. The expression vector for the recombinant protein composed of CBM-54 of ChiW (Val198 to Phe449) was prepared by DNA truncation from the ChiW-SLHd expression vector with the KOD-Plus-Mutagenesis Kit (Toyobo, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FPU-7 (Fig 1) were overexpressed in Escherichia coli ( E . coli ) and purified as described previously [12]. The expression vector for the recombinant protein composed of CBM-54 of ChiW (Val198 to Phe449) was prepared by DNA truncation from the ChiW-SLHd expression vector with the KOD-Plus-Mutagenesis Kit (Toyobo, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic and biochemical analyses of the FPU-7 strain have revealed that the bacterium secretes at least seven chitinases, one of which is a unique high-molecular-mass (150 kDa) chitinase, termed ChiW. This enzyme has three surface-layer homology (SLH) domains (~18 kDa) (Fig 1); it is specifically expressed on the surface of the bacterial cell and degrades chitin [11, 12]. In general, the SLH domains are composed of three repeats of highly conserved sequences and bind noncovalently to glycan backbones of the peptidoglycan of Gram-positive bacteria, whereupon the cell wall is surrounded by the congregated proteins with SLH domains as a cell envelope or surface layer [13].…”
Section: Introductionmentioning
confidence: 99%
“…DAU101 [16], B. licheniformis [17], Paenibacillus sp. [18], Sanguibacter antarcticus [19], and Stenotrophomonas maltophilia [4]. However, most reported chitinases belong to endochitinases, while a few exochitinases were found in bacteria such as Thermococcus chitonophagus [7], Microbispora sp.…”
Section: Introductionmentioning
confidence: 99%
“…[16]. Until now, Paenibacillus species have been reported to produce some endochitinases [3,11-14,18,21], but no exochitinase from Paenibacillus species has been found.…”
Section: Introductionmentioning
confidence: 99%
“…(30), Paenibacillus sp. (31)(32)(33)(34)(35)(36), Clostridium sp. (37)(38)(39)(40)(41)(42)(43)(44), Thermoanaerobacterium sp.…”
mentioning
confidence: 99%